α-Synuclein levels modulate Huntington's disease in mice - Corrochano, Silvia (Oxford University Press, 2012)
α-Synuclein and mutant huntingtin are the major constituents of the intracellular aggregates that characterize the pathology of Parkinson's disease (PD) and Huntington's disease (HD), respectively. α-Synuclein is likely to be a major contributor to PD, since overexpression of this protein resulting from genetic triplication is sufficient to cause human forms of PD. We have previously demonstrated that wild-type α-synuclein overexpression impairs macroautophagy in mammalian cells and in transgenic mice. Overexpression of human wild-type α-synuclein in cells and Drosophila models of HD worsens the disease phenotype. Here, we examined whether α-synuclein overexpression also worsens the HD phenotype in a mammalian system using two widely used N-terminal HD mouse models (R6/1 and N171-82Q). We also tested the effects of α-synuclein deletion in the same N-terminal HD mouse models, as well as assessed the effects of α-synuclein deletion on macroautophagy in mouse brains. We show that overexpression of wild-type α-synuclein in both mouse models of HD enhances the onset of tremors and has some influence on the rate of weight loss. On the other hand, α-synuclein deletion in both HD models increases autophagosome numbers and this is associated with a delayed onset of tremors and weight loss, two of the most prominent endophenotypes of the HD-like disease in mice. We have therefore established a functional link between these two aggregate-prone proteins in mammals and provide further support for the model that wild-type α-synuclein negatively regulates autophagy even at physiological levels.